VD_FINDINFO Jug / 2020 / 148 vom 24. Februar 2016 - VD Tribunal cantonal (2016)
DÉFAUTCONTUMACE, PRESCRIPTION, FRAIS DE LA PROCÉDURE, INDEMNITÉ POUR DÉTENTION | 97 al. 3 CP, 369 al. 1 CPP (CH), 369 al. 3 CPP (CH), 426 al. 2 CPP (CH), 431 CPP (CH)